KAJIAN ETNOGRAFI: ANALISIS SHARED VALUES GENERASI Y DAN GEN Z DALAM MENGIKUTI OLAHRAGA POUND FIT (Studi Kasus Pound Fit Pound Glory Jakarta) - Wicaksono, Muhammad Haston Samudra; Putri, Juandela Herina; Oktarini, Dwi Indah; Heikal, Jerry (Jurnal Media Akademik (JMA), 2024)
Currently, pound fit becomes popular sport in society, specifically for generation Y and Z. Both generations have significant characteristic differences in common beliefs and behaviors. Through the unique behavior pound fit participation in the Jakarta region, the researchers are interested in studying the shared values of Y and Z generation to choose the Pound Fit as their sport selection (Case Study Pound Fit Pound Glory Jakarta). This research uses a qualitative method with an ethnographic approach. Data collection used observation and interview methods with 4 respondents representing Y and Z generation at Club Pound Glory. The result depicts each generation has a unique perspective in determining the Pound Fit club location. However, Gen Y and Z have some similar shared values to choose the Pound Fit site, for instance, due to relieving stress and strategically the respondents have the value to keep staying at Pound Glory without any plan to move in another pound fit club.